Communication Strategy of the Indonesian Ministry of Religious Affairs in the Performance and Affirmation Assistance Program (BKBA) through the REP-MEQR Project - Heru Susanto; Afdal Makkuraga Putra (COMMICAST, 2025)
The rapid expansion of digital media has transformed government communication practices; however, its strategic application in large-scale education reform programs remains underexplored. In Indonesia, the Ministry of Religious Affairs utilizes digital platforms, particularly YouTube, to disseminate information on the Performance and Affirmation Assistance Program (BKBA) under the Realizing Education’s Promise Madrasah Education Quality Reform (REP-MEQR) Project. Despite the program’s critical role in reducing disparities among more than 78.000 madrasahs, empirical studies rarely examine how digital communication strategies function within a multi-level bureaucratic structure or how they are perceived by beneficiaries. This study aims to analyze the Ministry’s digital communication strategy in socializing the BKBA Program through video-based content and to assess responses from recipient madrasahs. The study contributes to the literature on digital government communication by providing empirical evidence on strategy effectiveness in a tiered governance context. A qualitative research design was employed, involving field observations, in-depth interviews with Ministry officials, project managers, and madrasah representatives, as well as content analysis of official YouTube materials. The findings reveal that the Ministry applies a systematic and tiered communication strategy combining digital platforms, technical guidance, and direct socialization. While generally effective, the strategy faces challenges related to unequal digital literacy, infrastructural limitations, and inconsistent regional support. Nevertheless, beneficiary madrasahs report positive impacts, particularly improvements in educational infrastructure and institutional capacity. The study concludes that coordinated, multi-level digital communication can enhance government program outreach, provided that inclusivity, contextualization, and regional capacity strengthening are prioritized.